Ball Burnishing effects on hardness and residual stresses in UDIMET 720 pieces. Issue 1 (October 2021) - Rue, J; Velazquez, E; Marques, J; Llumà, J; Jerez, R; Travieso, J A
Abstract: Ball burnishing can be used to increase superficial hardness in treated materials. The aim of this paper is to study its influence over a nickel-based superalloy, UDIMET 720. To do this, the specimens where burnished and their hardness is analyzed, before and after the process, in the micro and nanometric scales. To corroborate findings, residual stresses are measured by the X-ray diffraction technique. This process has been found to be able to increase superficial hardness values up to 31% in the superalloy. Results also show that the hardness differential between the micro and nanometric scale is around 13%. An increase in compressive stress has been measured after the procedure, which can help explain this increase in hardness.